KAJIAN PENYERAPAN LOGAM BERAT AIR RAKSA (Hg) DENGAN MENGGUNAKAN KARBON AKTIF BATUBARA SUB-BITUMINUS YANG DIKARBONISASI (COALITE) - Solihin, Solihin; Chamid, Chusharini; Sugarba, Garlan (Bumi Lestari, 2009)
One of diversification usage of coal is made for carbon active. The main element in coal which is very useful for carbon active is carbon (C) as other raw materials such as bone, coffee bean, coconut shell, etc. This research used carbonized coal from PT.Bukit Asam as a media to absorb methyl mercury (CH3Hg+2) solution. The carbonized coal has iodine number of ± 386 mg/gram after it was activated at 9000C for 1 hour. It has an adsorption level of 70-80% because the SEM photograph showed a pore size of coarse fraction higher than fine fraction. The degree of saturation is influenced by the grain size of the coal carbon active where the saturation degree of coarse fraction was relatively faster than the fine fraction. Moreover, weightier and bigger debit of carbon active could adsorb higher MeHg concentration.
Keywords: carbonization; carbon active; adsorption; coalite; methyl mercury; iodine number